Functional Nanomaterials for Healthcare - Terracciano, Monica; Rea, Ilaria; Borbone, Nicola; Tramontano, Chiara (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
"Functional Nanomaterials for Healthcare" is a collection showcasing cutting-edge research in advanced nanomaterials for healthcare applications. As healthcare evolves through science and innovation, these articles provide the latest insights into nanomaterial applications. Researchers have tailored nanomaterials for improved diagnostics, medical imaging, precise drug delivery, tissue engineering, and groundbreaking theranostics. This compilation, written by experts, explores advanced nanomaterial synthesis, functionalization, characterization, and diverse medical uses. Dive into this significant contribution to the field, offering a comprehensive overview of the latest innovations in healthcare nanomaterials for researchers, students, and healthcare professionals.